PENGARUH RATIFIKASI KONVENSI MINAMATA TERHADAP DARURAT MERKURI DI INDONESIA - Aditya Solihin; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is a contemporary political study which describes The influence of the Minamata Convention on Mercury Emergency in Indonesia. This research will focus on how a treaty makes an effect on a country. This study is interesting because it describes about Minamata treaty and mercury emergency in Indonesia. Minamata Convention is an international agreement designed to protect human health, aims to manage mercury efficiently, effectively and coherently, while members strive for total elimination.This is qualitative research which uses descriptive methods, and collected data from some resources like books, journals, official publications and its relevant websites. This paper uses the constructivism perspective and International Treaty Theory. The object in this research is environment an main actor in International Relations.The result of this research shows that The influence of the Minamata Convention on mercury emergencies in Indonesia, which can reduce mercury emergency status in Indonesia. Ratification of Law No. 11 of 2017 concerning Ratification of the Minamata Convention on Mercury. Reduction in mercury consumption, product replacement / removal, waste management and mercury control at the source.the use of technology in the remediation of land contaminated with mercury is adsorption, phytoremediation, stabilization, and immobilization.Keywords: Treaty, Mercury, Constructivism, Ratification, Minamata Covention